Young’s Electron Experiment Enigma - Schatten, Kenneth H. (European Journal of Applied Sciences, 2023)
This paper focuses on a long-standing problem in physics that originated more than two centuries ago. In 1802 Young noticed numerous bright and dark bands formed behind a metal sheet containing a pair of slits, when it was illuminated by candlelight. Advances in understanding the nature of light, the bands could be understood as “light interference patterns.” Nevertheless, in the mid-20th century, another paradox arose when individual electrons fell upon the double slit configuration. It was not clear how individual electrons could create the same banded patterns. Yet the new quantum physics theory was at the peak of physics’ popularity. As a result, a special moniker was created that allowed such idiosyncrasies: “wave-particle duality.” Under its banner, waves could act as particles and vice-versa. This behavior failed “locality,” essentially meaning local reality or relativity, as each electron, considered as an indivisible particle, could not then pass through both slits simultaneously. This paper offers a modern Quantum Field Theory (QFT) approach showing how modern Quantum Field Theory can resolve this electron enigma.